Analysis of Mitraguna Financing for Civil Servants through Take Over Mechanism at Bank BSI - Rahmatullah, Nursalam (UIN Siber Syekh Nurjati Cirebon, 2025)
Bank Syariah Indonesia (BSI), as an Islamic financial institution, provides takeover financing services to facilitate the transition of customers from conventional banks to Sharia-compliant banking. One of its flagship products, the Mitraguna facility, has attracted significant public interest in switching to the Islamic financial system. This study aims to analyze the legal compliance of Bank Syariah Indonesia in implementing Fatwa No. 31/DSN-MUI/VI/2002 on Debt Transfer, issued by the National Sharia Council of the Indonesian Ulema Council (Dewan Syariah Nasional Majelis Ulama Indonesia / DSN-MUI), particularly in the context of takeover financing through the Mitraguna facility for civil servants. Using a normative-empirical method with a descriptive-analytical approach, data were collected through interviews with BSI employees (Basuki Rahmat Branch, Palu City), BSI’s official website, and library research. The findings indicate that the implementation of takeover financing at BSI through the Mitraguna facility aligns with the provisions of the fatwa, specifically through the use of the musyarakah mutanaqisah (MMQ) contract, which corresponds to Alternative II outlined in the DSN-MUI fatwa. This research is expected to contribute to the development of Sharia economic law and serve as a reference for ensuring Sharia compliance in Islamic financial institutions.Keywords: Mitraguna; Civil Servants; Takeover Financing; Bank Syariah Indonesia